Minimizing Potential Losses in KPR Hijrah Through a 7-Step Approach - Nor Rokhmawati; Mohammad Dliyaul Muflihin; Imam Buchori; Ade Irma Suryani Lating (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2026)
This study aims to analyze the risk management strategy of Hijrah Muamalat KPR financing at Bank Muamalat KC Surabaya and the efforts made to minimize potential losses. The research method used is descriptive qualitative, conducted through interviews and direct documentation at Bank Muamalat KC Surabaya. The results show that the implementation of risk management in Hijrah Muamalat KPR financing has been carried out well. The risk management strategy process includes: first, determining the context, which involves understanding customer criteria and marketing networks. Second, risk identification by applying the 5C principle. Third, risk analysis, which evaluates the likelihood of risks occurring and their impact on bank operations. Fourth, risk evaluation with the main focus on maintaining the safety of customer collectability. Fifth, risk management is carried out through telecall activities, customer visits, and restructuring. Sixth, risk monitoring is conducted to periodically observe customer conditions. Seventh, effective communication among teams must be well established. This study implies that a good understanding of customer context and marketing networks can improve the quality of financing analysis. The consistent application of the 5C principle helps the bank select eligible customers, thereby minimizing the possibility of non-performing financing. In addition, structured risk analysis and evaluation encourage more accurate and data-driven decision-making.